Design of delta-sigma modulator for ultrasound imaging - Song, Pengyu (2009)
The design and implementation of a high speed continuous-time delta-sigma modulator is presented in this report. The modulator is designed for a portable ultrasound digital beamformer to digitize ultrasound signal centered at 3.5MHz with fractional bandwidth of 0.6. A CMOS third-order low-pass modulator was simulated and implemented at 200MHz sampling frequency. An improved low power transconductor with reduced mobility degradation was designed and realized. With full circuit simulation, the modulator achieves a dynamic range of 59.6dB and consumes only 4.20mW RMS power at 1.8V supply voltage. The layout was implemented using Chartered 0.18μm CMOS process. The core layout occupies 0.073mm2 and the entire die including 24 pads occupies 1.54mm2. Comparing with the existing circuits, the proposed structure dissipates relatively lower power and achieves comparable resolution.